A non-randomized comparative study of olfactory and gustatory functions in children who recovered from COVID-19 (1-year follow-up) - Namazova-Baranova, Leyla; Karkashadze, George; Zelenkova, Irina; Vishneva, Elena; Kaytukova, Elena; Rusinova, Dina; Ustinova, Natalia; Sergienko, Natalia; Nesterova, Yulia; Yatsyk, Leonid; Kratko, Dmitrii; Gubanova, Svetlana; et al. (Frontiers in Pediatrics, 2022)
The experimental group included 68 children over 6 years of age who had recovered from COVID-19. The control group included 22 children over 6 years of age who have never had COVID-19. Research methods included neurological examination, verification of cognitive status, examination by an otolaryngologist, and smell and taste assessment. The examination was performed 6–8 weeks after COVID-19 recovery and after 1 year in some patients. Children who recovered from COVID-19 had a reduction in their ability to smell compared to children who had never had COVID-19. The olfactory thresholds and taste identification scores after recovery from COVID-19 were identical, whether the parents had reported anosmia in their children during COVID-19 or not, and irrespective of hyperthermia level and the presence or absence of headache and hyperhidrosis during COVID-19. Analysis of correlation with neuropsychiatric symptoms showed no differences in the olfactory thresholds in children irrespective of the presence of neuropsychiatric symptoms (tics, tremors, enuresis, compulsive movements, seizures, speech disorders, attention deficit, and easy fatigability) both in general, and in particular among subjects performing or not any compulsive movements, and experiencing or not a combination of easy fatigability and daytime sleepiness. Evidence suggests that in children and adolescents, partial hyposmia is associated with depressive symptoms, varying in severity from low to high, but symptoms of depression were not caused by COVID-19 infection itself. Analysis in subgroups with different degrees of state and trait anxiety did not reveal any significant differences in the olfactory threshold. A re-examination of 21 children was performed after 1 year. An objective olfactometric examination showed that the sensitivity to odorants increased significantly. In 1 year, we compared the thresholds of smell in children who had COVID-19 and those who did not have this disease: olfactory sensitivity after COVID-19 in children is restored to normal values. Schulte correction test showed that none of 14 children with asthenic manifestations in the form of fluctuations or exhaustion when performing the test immediately after COVID-19 had these manifestations after 1 year. Thus, asthenization of cognitive activity was recorded within the next 1.5 months after suffering from COVID-19 but was absent after 1 year.